Pekerja sosial sebagai agen perubahan: Studi kasus peran pekerja sosial di perpustakaan - Gemma Hanggarsih Tiftazani; Asep Saeful Rohman (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
This study is intended to describe social workers as agents of change. Social workers as a profession in Indonesia is still synonymous with the social profession which means working socially, done with voluntarily and not expecting an intention. The scope of this study is on volunteer social workers in rural libraries or in prisons libraries. The method used in this study is descriptive with a qualitative approach. Data acquisition through interviews, observation and literature review. The results illustrate the point in the library become the most desirable place for inmates to make the most of their time in search of entertainment and knowledge. The village library can be a place for people to engage actively in activities such as practicing computers, preserving local culture and knowledge, and entrepreneurship training. The conclusion of this study is that libraries, both village libraries and prison libraries can contribute to improving the quality of life of the community. The Profession of Social Workers participates and functions as a agent of change by involving themselves as educators, facilitators, community facilitators and partners for the government and the private sector